The Influence of Job Rotation, Leadership, and Career Development on Employee Performance - Sihombing, Anggi Hartaty; Ngaliman, Ngaliman; Luthfi, Andi (Zona Manajerial: Program Studi Manajemen (S1), 2022)
Immigration Office Class I Special TPI Batam. This Vertical Agency is a Technical Implementation Unit in Batam City under the auspices of the Ministry of Law and Human Rights of the Republic of Indonesia, the Immigration Office Class I Special for TPI Batam provides services to the community. The Immigration Office Class I Special TPI Batam provides services to the community with a very significant number of services and community participation every day, such as services in the issuance of immigration travel documents, immigration checks as well as immigration supervision and action. To realize these services, several efforts were made to improve the quality of the performance of the Immigration Office Class I Special TPI Batam employees. The purpose of this study was to determine the effect of job rotation, leadership and career development on the performance of the Immigration Office Special Class I TPI Batam, either partially or simultaneously. The research method used is quantitative and qualitative methods based on primary in the form of questionnaires and secondary data from agencies. The number of samples in this study were 170 respondents who were employees of the Class I immigration office specifically for TPI Batam. The data analysis technique was carried out by multiple linear regression analysis with the help of SPSS statistical tools. The results of the study found that internal rotation had a partially insignificant effect on employee performance. Career development partially significant effect on employee performance. Leadership partially significant effect on employee performance. Internal rotation, career development and leadership simultaneously have a significant effect on performance.